(Re)constructing Teacher Identity through the Contesting Narratives of ELT Associations - Ramesh Nair (The English Teacher, 2021)
Discussions in the mainstream media about the declining standard of English in Malaysia have focused on a variety of contributing factors, one of the more prominent being the quality of teaching. English language teachers have been central actors in these narratives and are often easy targets for assigning blame. Left uncontested, such narratives have the capacity to shape a damaging image of Malaysian English language teachers which can have lasting implications for the ELT profession in the country. Fortunately, alternative voices emerge to challenge narratives describing Malaysian English language teachers as inept and incompetent. In this paper, I examine such narratives as they are presented through multimodal texts published and circulated in the public domain by the Malaysian English Language Teaching Association. Drawing on the frameworks of Systemic-Functional Linguistics and visual grammar, I examine a series of posters disseminated through the association’s social media platforms. The analysis unpacks the language and images used in the posters, and reveals an alternative discourse in which these teachers are presented as trained professionals with expertise in their field of ELT. The study highlights the important role of ELT associations in representing its members by challenging emerging discourses which threaten the reputation of the profession.
Keywords: ELT associations, Systemic-Functional Linguistics, multimodal texts, teacher identity